2020
DOI: 10.1007/s40136-020-00275-w
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Validated Simulation Training Curriculum in Otolaryngology

Abstract: Purpose of Review Simulation-based training is an integral component of surgical training. It allows practice of technical skills within a safe environment without compromising patient safety. This article seeks to review current virtual and non-virtual reality simulation models within the literature and review their validation status. Recent Findings Many simulation models exist within otolaryngology and are currently being used for education. New models are also continuously being developed; however, validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…There are several examples of ENT simulation training, including nasal packing, flexible nasendoscopy, quinsy and tracheostomy. [30][31][32][33] All of these approaches have demonstrated that simulation provides a useful means to bridge the gap between theoretical knowledge and the ability to perform the skill on a real patient, something that learners in this study craved. This learning could be facilitated in a single day of teaching to meet the needs listed in Table 3, as well as taking into account the non-technical skills that were highlighted by junior interviewees.…”
Section: Discussionmentioning
confidence: 90%
“…There are several examples of ENT simulation training, including nasal packing, flexible nasendoscopy, quinsy and tracheostomy. [30][31][32][33] All of these approaches have demonstrated that simulation provides a useful means to bridge the gap between theoretical knowledge and the ability to perform the skill on a real patient, something that learners in this study craved. This learning could be facilitated in a single day of teaching to meet the needs listed in Table 3, as well as taking into account the non-technical skills that were highlighted by junior interviewees.…”
Section: Discussionmentioning
confidence: 90%